2019
DOI: 10.31234/osf.io/2j7ms
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paranoia, sensitisation and social inference: findings from two large-scale, multi-round behavioural experiments.

Abstract: 1The sensitisation model suggests paranoia is explained by over-sensitivity to 2 perceived threat in social environments. However, this has been difficult to test 3 experimentally. We report two pre-registered studies that tested i) the sensitisation 4 model as an explanation of paranoia, and; ii) the role of purported maintaining 5 factors in supporting social sensitisation. In study one, we recruited a large general 6 population sample (N=987) who serially interacted with other participants in multi-7round D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 57 publications
(85 reference statements)
3
33
1
Order By: Relevance
“…Social experiments using interactive game theory tasks have found that paranoia reduces the threshold for attributing harmful intent in ambiguous social exchanges [ 15 18 ]. More recently, Barnby et al [ 19 ] extended this work and additionally found that individuals high in paranoia were more likely to reduce high harmful intent attributions after a higher initial peak when interacting with partners who were consistently fair. This finding potentially suggested increased uncertainty of live paranoid social inferences in those with higher baseline pre-existing paranoid beliefs.…”
Section: Introductionmentioning
confidence: 85%
“…Social experiments using interactive game theory tasks have found that paranoia reduces the threshold for attributing harmful intent in ambiguous social exchanges [ 15 18 ]. More recently, Barnby et al [ 19 ] extended this work and additionally found that individuals high in paranoia were more likely to reduce high harmful intent attributions after a higher initial peak when interacting with partners who were consistently fair. This finding potentially suggested increased uncertainty of live paranoid social inferences in those with higher baseline pre-existing paranoid beliefs.…”
Section: Introductionmentioning
confidence: 85%
“…Following Barnby et al (2019a), we analysed the data using multi-model selection with model averaging (Burnham & Anderson, 2004;Grueber et al, 2011). The Akaike information criterion, corrected for small sample sizes (AICc), was used to evaluate models, with lower AICc values indicating a better fit (Grueber et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We developed a within-subjects, multi-trial modification on the Dictator game design used in previous studies to assess paranoia (Barnby et al, 2019a). Each participant played six trials against three different types of dictator.…”
Section: The Multi-round Dictator Gamementioning
confidence: 99%
See 2 more Smart Citations